Discovery of Suprathermal Ionospheric Origin Fe+ in and Near Earth's Magnetosphere. Issue 11 (14th November 2017) - Christon, S. P.; Hamilton, D. C.; Plane, J. M. C.; Mitchell, D. G.; Grebowsky, J. M.; Spjeldvik, W. N.; Nylund, S. R.
Abstract: Suprathermal (87–212 keV/e) singly charged iron, Fe +, has been discovered in and near Earth's ~9–30  R E equatorial magnetosphere using ~21 years of Geotail STICS (suprathermal ion composition spectrometer) data. Its detection is enhanced during higher geomagnetic and solar activity levels. Fe +, rare compared to dominant suprathermal solar wind and ionospheric origin heavy ions, might derive from one or all three candidate lower‐energy sources: (a) ionospheric outflow of Fe + escaped from ion layers near ~100 km altitude, (b) charge exchange of nominal solar wind iron, Fe +≥7, in Earth's exosphere, or (c) inner source pickup Fe + carried by the solar wind, likely formed by solar wind Fe interaction with near‐Sun interplanetary dust particles. Earth's semipermanent ionospheric Fe + layers derive from tons of interplanetary dust particles entering Earth's atmosphere daily, and Fe + scattered from these layers is observed up to ~1000 km altitude, likely escaping in strong ionospheric outflows. Using ~26% of STICS's magnetosphere‐dominated data when possible Fe +2 ions are not masked by other ions, we demonstrate that solar wind Fe charge exchange secondaries are not an obvious Fe + source. Contemporaneous Earth flyby and cruise data from charge‐energy‐mass spectrometer on the Cassini spacecraft, a functionally identical instrument, show that inner source pickup Fe + is likely not important at suprathermal energies. Consequently, we suggest that ionospheric Fe + constitutes at least a significant portion of Earth's suprathermal Fe +, comparable to the situation at Saturn where suprathermal Fe + is also likely of ionospheric origin. Key Points: The first in situ observations of suprathermal Fe + in and near Earth's magnetosphere are reported using 21 years of Geotail data A rare species, Fe + occurrence is positively associated with both geomagnetic ( Kp ) and solar ( F 10.7 ) activity indices Fe + of likely ionospheric origin dominates at Kp  < ~4; at Kp  > ~4, solar wind and/or inner source‐derived Fe + may contribute